PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN COMMUNITY BASED TOURISM SEBAGAI UPAYA PENGEMBANGAN WISATA DI KABUPATEN ACEH BARAT - Maulida, Desi; Kesha, Cut Nabilla; Safrida, Safrida (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
Tourism development certainly cannot be separated from the role of the community as development agents who in principle have the same authority and responsibility as the government in managing tourism. This concept is known as community-based tourism, namely tourism management that promotes active participation from the community. This research aims to examine development efforts carried out by the community as a form of participation in the development of halal tourism in West Aceh Regency and analyze the obstacles faced in tourism management. This research is descriptive qualitative research. There were 9 research informants from three sub-districts, namely Samatiga, Johan Pahlawan and Panton Reu sub-districts. Data collection was carried out by means of interviews, observation and documentation studies. The theory used in this research is the convergence model of communication with seven indicators, namely information, uncertainty, convergence, respect, mutual agreement, collective action, and network of relationships. The results of the study show that community participation in tourism development efforts in West aceh district is still relatively minimal. This is because some people still think that tourism management is still the full responsibility of the government. The obstacles identified in the implementation of tourism development include the belief that tourism management is still the government's responsibility, the assumption that tourism practices can violate the rules of Islamic law, and the lack of community competence in tourism management so that special training is needed to be provided to the community by government.